Mobility anisotropy in the herringbone structure of asymmetric Ph-BTBT-10 in solution sheared thin film transistors. Issue 22 (23rd May 2021) - Tamayo, Adrián; Hofer, Sebastian; Salzillo, Tommaso; Ruzié, Christian; Schweicher, Guillaume; Resel, Roland; Mas-Torrent, Marta
Abstract : Thin films of Ph-BTBT-10 are deposited by solution shearing at low and high coating velocities. Films coated at low speed are anisotropic, while the high coating speed films are less ordered but more homogenous and electrically isotropic. Abstract : Thin films of the organic semiconductor Ph-BTBT-10 and blends of this material with polystyrene have been deposited by a solution shearing technique at low (1 mm s −1 ) and high (10 mm s −1 ) coating velocities and implemented in organic field-effect transistors. Combined X-ray diffraction and electrical characterisation studies prove that the films coated at low speed are significantly anisotropic. The highest mobility is found along the coating direction, which corresponds to the crystallographic a -axis. In contrast, at high coating speed the films are crystallographically less ordered but with better thin film homogeneity and exhibit isotropic electrical characteristics. Best mobilities are found in films prepared at high coating speeds with the blended semiconductor. This work demonstrates the interplay between the crystal packing and thin film morphology and uniformity and their impact on the device performance.